2022
DOI: 10.3389/fgene.2022.1037011
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of lung adenocarcinoma classification and risk model based on necroptosis-related genes

Abstract: Lung adenocarcinoma (LUAD) is the most widely known histological subtype of lung cancer. Its classification is significant for the characteristic evaluation of patients. The aim of this research is to assess the categorization of LUAD and its risk model based on necroptosis and to investigate its potential regulatory mechanisms for diagnosing and treating LUAD. According to the expression profile data along with the clinical information related to LUAD from The Cancer Genome Atlas (TCGA) and Gene Expression Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This algorithm calculated the relative abundance of 22 immune cell types in each LIHC sample. ESTIMATE is a tool for predicting stromal score [ 15 , 16 ], which refers to the presence of stroma in tumor tissue, with the immune score suggesting the infiltration of immune cells in tumor tissue and the estimated score indicating tumor purity. The CIBERSORT algorithms and ESTIMATE algorithm were adopted to clarify the cell composition of 22 immune cell types from HCC tissues based on genomic profiles.…”
Section: Methodsmentioning
confidence: 99%
“…This algorithm calculated the relative abundance of 22 immune cell types in each LIHC sample. ESTIMATE is a tool for predicting stromal score [ 15 , 16 ], which refers to the presence of stroma in tumor tissue, with the immune score suggesting the infiltration of immune cells in tumor tissue and the estimated score indicating tumor purity. The CIBERSORT algorithms and ESTIMATE algorithm were adopted to clarify the cell composition of 22 immune cell types from HCC tissues based on genomic profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor cells have signi cant metabolic characteristics, and alterations in apoptotic characteristics and signaling characteristics can affect the prognosis of patients. For example, Wang Z et al (Wang et al 2023)reported a metabolism-related prognostic signature that predicted the overall survival of LUAD patients, Xie Y(Xie et al 2024) reported a signaling-related prognostic signature that predicted the overall survival of LUAD patients, and Wu G (Wu et al 2022) reported an apoptosis-related prognostic feature that predicts overall survival in patients with LUAD.LUAD has a complex and heterogeneous tumor microenvironment, which includes blood vessels, cancer cells, immune cells, and stromal cells (Zhao et al 2022).TME plays an important role in the therapeutic process of patients with LUAD. It has been suggested that Immune checkpoint inhibitors(ICI) resistance may be driven by loss of antigen presentation occurring in antigen-presenting cells within the TME or in cancer cells and is often associated with acquired genetic mutations (Chowell et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CALM1 and PGLYRP1 might play crucial roles in the occurrence and development of LUAD. Previous studies ( Zhang et al, 2022 ; Wu et al, 2022 ) solely relied on bioinformatics analysis. However, we performed RT-qPCR experimental validation, which confirmed our findings from bioinformatics analysis, thus increasing the credibility of our results.…”
Section: Discussionmentioning
confidence: 99%